Pemberian Pakan Bahan Kering Berkuantitas Terbatas Selama Empat Minggu Tidak Menganggu Kesehatan dan Reproduksi Kambing Kacang Jantan Dewasa (FEEDING WITH A RESTRICTED QUANTITY OF DRY MATTER OVER FOUR WEEKS IS NOT DETRIMENTAL TO HEALTH AND REPRODUCTION IN - Widiyono, Irkham; Suwignyo, Bambang; Sarmin, Sarmin; Susmiyati, Trini (Jurnal Veteriner, 2017)
The study was aimed to investigate the effects of restricted feeding for four weeks on some bloodchemistry and seminal parameters in kacang goats. Six adult clinically healthy male kacang goats wereused in this study. Each animal was kept in individual box for 12 weeks. Animal was fed with aerial partof peanut plant and concentrate with ratio of 60:40. The experiment was devided into two feeding periods,fullfeeding and restricted feeding. After four weeks adaptation (week 1-4), each animal was fullfed formaintenance plus medium activity (a quantity of dry matter at the level of 3% of body weight) for fourweeks (week 5-8) and then was fed only 50% of the fullfeeding nutritional level for the following four weeks restricted feeding period (week 9-12). During the experiment, drinking water was supplied ad libitum.Each animal was ejaculated at weekly intervals by means of standard artificial vagina for small ruminant.Blood and semen samples were collected at the end of the ad libitum and restricted feeding period for bloodchemistry and seminal parameters analyses. Statistical differences were determined by paired t-test. A0.05 probability level was used as criterion to describe statistically significant differences. Restrictedfeeding at the dry matter intake level of 1.5% body weight for four weeks did not result in significantchanging of serum glucose and total protein concentrations as well as seminal parameters. The level ofblood chemistry and seminal parameters during the feed restriction period were within the values reportedfor clinically healthy goats. It is concluded that feeding with a restricted quantity of dry matter at the levelof 1.5% of body weight for four weeks is not detrimental to health and reproduction in male kacang goats.
Keywords: blood chemistry; feed restriction; kacang goat; semen